2017
DOI: 10.1039/c6cy02110g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms governing selective hydrogenation of acetylene over γ-Mo2N surfaces

Abstract: We demonstrate that the selective hydrogenation of acetylene depends on energy profile of the partial and full hydrogenation routes and the thermodynamic stability of adsorbed C2H2 in comparison to C2H4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Based on DFT calculations, Dlugogorski and co-workers also observed stable O atoms adsorbed on the N-vacant Mo sites during NO reduction and H atoms adsorbed strongly on the surface N sites during H 2 dissociation on the Mo 2 N(111) surface. 43 , 60 Experimental studies performed by He et al revealed the transformation of γ-Mo 2 N into a Mo 2 O x N y phase in the presence of NO, and this phase can be reduced back to γ-Mo 2 N by H 2 . 61 Thus, in Table 2 , the removal process of adsorbed oxygen atoms on the Mo 2 N surface by H 2 to form H 2 O is reported.…”
Section: Resultsmentioning
confidence: 99%
“…Based on DFT calculations, Dlugogorski and co-workers also observed stable O atoms adsorbed on the N-vacant Mo sites during NO reduction and H atoms adsorbed strongly on the surface N sites during H 2 dissociation on the Mo 2 N(111) surface. 43 , 60 Experimental studies performed by He et al revealed the transformation of γ-Mo 2 N into a Mo 2 O x N y phase in the presence of NO, and this phase can be reduced back to γ-Mo 2 N by H 2 . 61 Thus, in Table 2 , the removal process of adsorbed oxygen atoms on the Mo 2 N surface by H 2 to form H 2 O is reported.…”
Section: Resultsmentioning
confidence: 99%
“…Altarawneh et al [47], used computational methods to study mechanism of the selective hydrogenation C 2 H 2 over γ-Mo 2 N to C 2 H 4 rather than complete hydrogenation to the corresponding alkane.…”
Section: Transition Metal Nitrides As Catalystmentioning
confidence: 99%
“…35 The γ-Mo 2 N that has special crystal and electronic structure was usually used as a support in various catalytic processes but not including the WGS reaction. 12,36−38 Although its surface is partially oxidized during reactions, the γ-Mo 2 N was found to maintain a sustained and stable surface structure, 39,40 which makes it a promising candidate as the substrate for the heterostructure.…”
Section: ■ Introductionmentioning
confidence: 99%